From invocation to indictment: Analyzing hate speech elements in a social media prayer - Surahmat, Surahmat; Arimi, Sailal; Susilowati, Novi Eka; Imamah, Fardan Mahmudatul (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
This study investigates a controversial Facebook post prosecuted under Indonesian hate speech law, focusing on a “bad prayer” directed at the president during the 2019 election period. This research was a case study of a hate speech that the Tembilahan District Court, Indragiri Hilir, Riau, decided. The data was collected from the case trial on the website of the Supreme Court of the Republic of Indonesia and the associated Facebook group.  Employing semantic, sociolinguistic, and pragmatic analyses, the research explores how religious language can serve as a vehicle for politically motivated hate speech. Findings indicate that the expression, namely “Congratulations on the presidential inauguration, may he meet his end as soon as possible. Amen", constitutes minor hate speech by violating politeness principles and implying negative social judgment. The statement is motivated by the competition between two candidates in the 2019 presidential election, where the accused disapproved of the elected President Joko Widodo. This interdisciplinary approach contributes to forensic linguistics by introducing the concept of “bad prayer” and examining its sociopolitical and legal implications in Southeast Asian digital discourse.